Symbolic meaning of Barikan tradition in realizing maritime culture preservation of the Mojo Village, Pemalang - Dewi, Rizky Septiana; Atmadja, Hamdan Tri; Rodiyah, Rodiyah (JESS (Journal of Educational Social Studies), 2022)
Coastal community is people who live and carry out socio-economic activities related to the coastal and its resources. One of the cultural wealth owned by the coastal community is sea alms. The purpose of this paper is to describe the symbolic meaning of the Barikan tradition in Mojo Village, describe how the community interprets the Barikan tradition, and find out the factors that influence the Barikan tradition in Mojo Village that still exists amid modernization. This research is expected to find and develop knowledge related to symbolic meaning in the Barikan tradition as well as contribute to the development of science, especially Social Studies Education, which includes social change. Data sources are informants, documents, and phenomena or events. The results showed that the symbolic meaning of the Barikan Tradition was in the buffalo head, tumpeng, and the offerings tradition. The village head interprets the barikan tradition as identity, the fishers as a ritual, and teenagers as entertainment. The factors that influence the Barikan tradition to continue to exist are the historical and mythical factors that have developed in the community. Thus far, there has been no change in the Barikan tradition even though the times have led to modernization.